Electroporation-mediated interleukin-10 overexpression in skeletal muscle reduces acute rejection in rat cardiac allografts. - Tavakoli, R; Gazdhar, A; Pierog, J; Bogdanova, A; Gugger, M; Pringle, I; Gill, DR; Hyde, S; Genoni, M; Schmid, R (2006)
OBJECTIVES: Human interleukin 10 (hIL-10) may reduce acute rejection after organ transplantation. Our previous data shows that electroporation-mediated transfer of plasmid DNA to peripheral muscle enhances gene transduction dramatically. This study was designed to investigate the effect of electroporation-mediated overexpression of hIL-10 on acute rejection of cardiac allografts in the rat. METHODS: The study was designed to evaluate the effect of hIL-10 gene transfer on (a) early rejection pattern and (b) graft survival. Gene transfer was achieved by intramuscular (i.m.) injection into the tibialis anterior muscle of Fischer (F344) male recipients followed by electroporation 24 h prior to transplantation. Heterotopic cardiac transplantation was performed from male Brown Norway rat to F344. Four groups were studied (n = 6). Treated animals in groups B1 and B2 received 2.5 microg of pCIK hIL-10 and control animals in groups A1 and A2 distilled water. Graft function was assessed by daily palpation. Animals from group A1 were sacrificed at the cessation of the heart beat of the graft and those in group B1 were sacrificed at day 7; blood was taken for ELISA measurement of hIL-10 and tissue for myeloperoxidase (MPO) measurement and histological assessment. To evaluate graft survival, groups A2 and B2 were sacrificed at cessation of the heart beat of the graft. RESULTS: Histological examination revealed severe rejection (IIIB-IV) in group A1 in contrast to low to moderate rejection (IA-IIIA) in group B1 (p = 0.02). MPO activity was significantly lower in group B1 compared to group A1 (18 +/- 7 vs. 32 +/- 14 mU/mg protein, p = 0.05). Serum hIL-10 levels were 46 +/- 13 pg/ml in group B1 vs. 0 pg/ml in group A1. At day 7 all heart allografts in the treated groups B1 and B2 were beating, whereas they stopped beating at 5 +/- 2 days in groups A1 and A2 vs. 14 +/- 2 days in group B2 (p = 0.0012). CONCLUSIONS: Electroporation-mediated intramuscular overexpression of hIL-10 reduces acute rejection and improves survival of heterotopic heart allografts in rats. This study demonstrates that peripheral overexpression of specific genes in skeletal muscle may reduce acute rejection after whole organ transplantation.